Effects of sexual dimorphism and landscape composition on the trophic behavior of Greater Prairie-Chicken - Blanco-Fontao, Beatriz; Sandercock, Brett K.; Obeso, José Ramón; McNew, Lance B.; Quevedo, Mario (My University, 2014)
Partitioning of ecological niche is expected in lekking species that show marked sexual size dimorphism as a consequence of sex-specific ecological constraints. However, niche partitioning is uncertain in species with moderate sexual dimorphism. In addition, the ecological niche of a species may also be affected by landscape composition; particularly, agricultural fragmentation may greatly influence the trophic behavior of herbivores. We studied trophic niche variation in Greater Prairie-Chickens (Tympanuchus cupido), a grouse species that shows moderate sex-dimorphism. Greater Prairie-Chickens are native to tallgrass prairies of North America, although populations persist in less natural mosaics of cropland and native habitats. We used stable isotope analysis of carbon and nitrogen in blood, claws and feathers to assess seasonal differences in trophic niche breadth and individual specialization between male and female Greater Prairie-Chickens, and between birds living in continuous and fragmented landscapes. We found that females showed broader niches and higher individual specialization than males, especially in winter and autumn. However, differences between females and males were smaller in spring when birds converge at leks, suggesting that females and males may exhibit similar feeding behaviors during the lekking period. In addition, we found that birds living in native prairies showed greater annual trophic variability than conspecifics in agricultural mosaic landscapes. Native habitats may provide greater dietary diversity, resulting in greater diversity of feeding strategies.
Keywords: Sexual dimorphism; Greater Prairie- Chicken